Role of brain tissue oxygenation (PbtO2) in the management of subarachnoid haemorrhage: a scoping review protocol - Mauro Oddo; Fabio Silvio Taccone; Marco Fiore; Jacques Creteur; Elisa Bogossian (BMJ Open)
Introduction In patients with subarachnoid haemorrhage (SAH), the initial brain oedema and increased blood volume can cause an increase in intracranial pressure (ICP) leading to impaired cerebral perfusion and tissue hypoxia. However, ICP monitoring may not be enough to detect tissue hypoxia, which can also occur in the absence of elevated ICP. Moreover, some patients will experience tissue hypoxia in a later phase after admission due to the occurrence of delayed cerebral ischaemia. Therefore, the measurement of brain oxygenation using invasive techniques has become of great interest. This scoping review seeks to examine the role of brain tissue oxygenation in the management of patients with SAH, mapping the existing literature to identify areas for future research.Methods and analysis This scoping review has been planned following the Joanna Briggs Institute recommendations and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The literature search will be performed using several databases: Medline, EMBASE, the Cochrane Central Register of Controlled Trials and Grey literature. The database searches are planned from the inception to May 2020. Two reviewers will independently screen titles and abstracts, followed by full-text screening of potentially relevant articles with a standardised data extraction. Articles eligible for the inclusion will be discussed with a third reviewer.Ethics and dissemination This paper does not require ethics approval. The results of our evaluation will be disseminated on author’s web sites. Additional dissemination will occur through presentations at conferences, such as courses and science education conferences, regionally and nationally, and through articles published in peer-reviewed journals.Scoping review registration Open Science Framework Registration: https://doi.org/10.17605/OSF.IO/ZYJ7R.Trial registration numberClinicalTrials.gov Identifier: NCT03754114.